Short-term comparison of intraarticular administration of IL-1 receptor antagonist and platelet-rich plasma for osteoarthritis treatment - Yasin Guler; Ersin Kuyucu; Adnan Kara; Omer Serdar Hakyemez; Ferhat Say; Ahmet Murat Bulbul (Medicine Science, 2023)
Osteoarthritis (OA) is a prevalent joint condition that affects areas such as the knee, hip, hand, and spine. In treating mild to moderate cases of OA, treatment options such as intraarticular corticosteroids, viscosupplementation, glucosamine and chondroitin sulfate, PRP, and IL-1Ra are commonly used. This study aimed to compare the effects of IL-1 receptor antagonist (IL-1Ra) and platelet-rich plasma (PRP) on patients with Kellgren-Lawrence (KG) stage 2-3 knee osteoarthritis in terms of Visual Analog Scale (VAS) and Knee injury and osteoarthritis outcome score (KOOS). Ninety patients with KG stage 2-3 knee primary osteoarthritis were divided into two groups, with one group receiving three intraarticular IL-1Ra injections and the other group receiving three PRP injections. VAS and KOOS scores were recorded at the beginning and after six months to evaluate clinical improvement. Both the IL-1Ra and PRP groups showed statistically significant improvement in all scores, including the VAS and KOOS. After six months, the KOOS score in the IL-1Ra group was significantly higher than the PRP group, while the first-year VAS score after treatment in the IL-1Ra group was significantly lower compared to the PRP group. The mean KOOS scores increased from 44.1 to 87.8 and 46.04 to 84.43 at the end of six months in both groups, while the mean VAS scores decreased from 7.27 to 1.02 and 7.29 to 1.71 in the IL-1Ra and PRP groups, respectively. Administering intra-articular IL-1Ra once a week for three weeks can effectively improve function and reduce pain in patients with Kellgren-Lawrence stage 2-3 osteoarthritis. However, more research is necessary to validate the use of IL-1 receptor antagonists in OA treatment. [Med-Science 2023; 12(2.000): 542-7]